Teaching the “Morally and Economically Destitute”:: 19th-Century Adult Education Efforts in Newfoundland - English, Leona (Acadiensis, 2012)
This article focuses on the education of adults in 19th century Newfoundland through an examination of the early adult education efforts, formal and informal, by the colonial missionaries and the Newfoundland government and church leaders. These efforts include the Society of the Propagation of the Gospel (SPG), the Newfoundland School Society (NSS), private tutors, various literary societies and religious associations, on-the-job training in factories, navigation classes and apprenticeships, and church night schools. The article emphasizes the motivations underlying the specific initiatives, as many of the organizations had economic and moral goals and they used education (formal and informal) to accomplish them.